INCLUSION OF CHILDREN WITH SPECIAL NEEDS IN THE SOCIAL AND EDUCATIONAL ENVIRONMENT - Shevchenko, Volodymyr (Mountain School of Ukrainian Carpaty, 2018)
In the article the author considers an important issue for modern education in Ukraine, which is in the process of reforming. Inclusion of children with special needs aims to identify opportunities for them in the social and educational environment. Also, to discover problems of adaptation, that means: analysis, synthesis, systematization and generalization methods. The author defines the concept of "socialization", "social environment" and "social and educational environment". He emphasizes the peculiarities of interaction of children with special needs and the social environment. The author notes that the integration and socialization of children with special needs is a complex and lengthy process. It requires significant changes in the attitude towards children with disabilities. They require not only pedagogical and psychological support and rehabilitation measures. They need proper conditions for actualization of their abilities, development of personal qualities and needs in social, moral and spiritual self-improvement. Inclusion of children with special needs in the social environment is to create psychological and pedagogical conditions for learning and communication, the interaction of such a child in an educational institution. The author of the article also notes that full-fledged education of children with special needs can not take place separately from the family. Therefore, the family is a very important and significant component for the socialization of children with special needs. It has the most important and most responsible role in this process. Specialists should help and support such families. The author finds that today the influence of parents of children with special needs on the system of providing educational and rehabilitation services and on making state decisions in this sphere is quite significant. The potential of their capabilities for maximizing integration of children into the social and educational environment needs to be revealed. Provision of specialized care and family support plays a vital role in strengthening social integration and promotes conditions that allow children to adapt to the social environment with the help of inclusive education.